Great Excavations: Methodological considerations arising after a major archaeological infrastructure project for the A14 Cambridge to Huntingdon Road Improvement Scheme - Alex Smith; Emma West; Stephen Sherlock; Kasia Gdaniec; David Bowsher (Internet Archaeology)
This short paper draws together and evaluates some of the main methodologies utilized within the different stages of the A14 project and provides some 'lessons learned' that may be useful for future archaeological projects, particularly those associated with large infrastructure. To deliver a more balanced methodological evaluation, perspectives from different project stakeholders are captured here: those of the client (National Highways and A14 IDT), principal archaeological contractor (MHI) and curator (Cambridgeshire Historic Environment Team; CHET).